The Effect of Sujok Complementary Therapy on The Intensity of Osteoarthritis Joint Pain in The Elderly in Sleman - Lestari Lestari; Nessy Anggun Primasari; Erika Nur Widiyanti (Journal of Nursing Invention, 2025)
Background: Osteoarthritis patients often experience dull or intermittent pain of unpredictable intensity that is initially related to activity and then becomes more constant over time, which is one of the most common chronic conditions and can be disabling. Sujok therapy is effective in reducing pain, especially osteoarthritis.